EFEKTIVITAS PENGEMBANGAN KAWASAN MINAPOLITAN DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT KECAMATAN SARONGGI KABUPATEN SUMENEP - Nur Inna Alfiyah; Ida Syafriyani (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2020)
Poverty is an endless problem to examine, various policy formulas have been issued to reduce and alleviate poverty. One of them is with the Minapolitan program which aims to develop economic zones to be more productive, so that the community is able to be independent. Sumenep as one of the areas chosen as the development of the minapolitan area, with the minapolitan program providing benefits for the government in efforts to reduce poverty levels in Sumenep especially in coastal areas where some people depend on sea products. This research method uses a descriptive method with a descriptive approach. The results showed that the minapolitan program, especially in the Saronggi District was able to provide change for the community, especially for the group of fish and seaweed farmers, these changes can be seen from the results of production produced so that it impacts on the economic independence of the community.